Density of electron states and volume of solution of hydrogen in SiC alloys - Gervasoni, Juana Luisa; Furnari, Juan Carlos (David Publishing Company, 2014)
Fil: Gervasoni, Juana Luisa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina